Rancang Bangun Jaringan Hotspot Menggunakan Manajemen Bandwidth Dan RTRW Net Dengan Metode Simple Queue Di Kelurahan Tanah Datar Kecamatan Pekanbaru Kota - Settian Dwi Cahaya; Noveri Lysbetti M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Research on Design of Hotspot Network Using Bandwidth Management has been done in Indonesia, but there is still a problem such as bandwidth monopoly. In this study the writer a design a Hotspot Network System Using Simple Queue Method to avoid monopoly in bandwidth. This research was conducted in RT 02 Kelurahan Tanah Datar, Pekanbaru City District by utilizing the writer’s personal Wifi. In this study research use 10 client as a subject to test the design with total bandwidth 30 Mbps, where its bandwidth divide in to 5 Mbps for admin and 25 Mbps for clients. The results obtained from this study 10 clients successfully connected to Wifi and there is no monopoly of bandwidth between clients Keyword : Simple Queue, Wifi, Client